The impact of bladder preparation protocols on post treatment toxicity in radiotherapy for localised prostate cancer patients - Yat Man Tsang; Peter Hoskin (Technical Innovations & Patient Support in Radiation Oncology, 2017)
Objective: This study compares the post radiotherapy related toxicity between the use of an empty and a full bladder preparation protocol in patients receiving radical radiotherapy for localised prostate cancer. Methods and materials: A retrospective review of patient treatment records in which they were treated with a standard radiotherapy schedule (60Gy/20 fractions) to prostates and base of seminal vesicles only and followed two different bladder preparation (empty and full) protocols was carried out. This included each patient's daily image guided radiotherapy (IGRT) setup, treatment time, bladder size on planning computed tomography, organs at risk dose volume histograms (OAR DVHs) and 12 months post treatment gastrointestinal (GI) and genitourinary (GU) toxicity data. Results: 20 patients were included. There were significant differences in IGRT setup between the two groups. Although treatment times of the two groups were not significantly different, 5/200 (2.5%) sessions were longer than 20 min in the full bladder group while this was not found in the other group. Associations between bladder preparation protocols and GI (p = 1.0) and GU (p = 0.6) toxicities were not statistically significant. The bladder size on planning CT was not significantly correlated to the GI (R = 0.06, p = 0.8) or GU (R = 0.27, p = 0.3) toxicity scores. No significant differences were found in OAR DVHs between patients with and without GI and GU toxicities. No grade 3/4 toxicities were reported. Conclusion: The empty bladder preparation approach has non-inferior acute and intermediate post RT GI and GU toxicities in patients treated for localised prostate cancer with advanced radiotherapy techniques compared to the full bladder preparation.